2019
DOI: 10.1053/j.gastro.2019.07.060
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Gut Microbiome Interactions in Service-Related Gastrointestinal and Liver Diseases of Veterans

Abstract: I n response to a Request for Applications to support meetings to develop a novel roadmap for the Department of Veterans Affairs with focus on gastrointestinal (GI) illnesses that primarily affect returning veterans, a team of GI experts was invited to address these medical conditions affecting Veterans. A meeting was held on May 17, 2019, in San Diego, California, focused at developing a roadmap for targeting gut-microbe interactions in service-related GI diseases of veterans. This meeting was funded by Offic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…However, it is also worth reviewing the potential that environmental exposures in Asian countries such as chemical toxins (Agent Orange), infections, or parasites may have contributed to the alteration of the gut microbiome. 11 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is also worth reviewing the potential that environmental exposures in Asian countries such as chemical toxins (Agent Orange), infections, or parasites may have contributed to the alteration of the gut microbiome. 11 …”
Section: Discussionmentioning
confidence: 99%
“…In a review of GI conditions in Veterans, the authors suggested that increased incidence of diarrhea in Veterans may be related to food- or water-borne pathogens or deployment-related stress, both of which can alter the gut microbiome in the short term, and contribute to disease in the long term, as infectious gastroenteritis is a risk factor for the development of IBS. 11 , 12 The authors also offer other suggestions for factors that may contribute to the development of GI disease in Veterans, such as chronic stress, infections, toxins, and nonsteroidal anti-inflammatory medications that contribute to leaky gut. However, further research is necessary to investigate the mechanisms underlying the development of GI disease in Veterans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In instances such as endurance activities, physical and environmental stress responses have been linked to dysbiosis (35)(36)(37). Comorbidities such as heat stress and physical exertion are commonly encountered by warfighters and have been linked with increased GI permeability (38).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Diet exerts a large effect on the gut microbiota composition, but some bacteria thrive independently of dietary changes by colonizing the mucus layer as a reservoir and are maintained regardless of food intake (14). Thus, microbiome-host studies could target this mucus layer reservoir as a starting point to characterize gut resilience, and a systems biology approach to determine gut microbe interactions in enteric disease, pain, and the gut-brain axis must be considered (36).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%